Gendering Women - Clisby, Suzanne; Holdsworth, Julia (Policy Press, 2021)
Available Open Access under CC-BY-NC-ND licence Gendering Women is an engaging and accessible account of how constructions of femininity fundamentally affect women's mental wellbeing through the life course. Led by women’s life history accounts of growing up and growing older in the north of England, this book shows how experiences of becoming and being a woman – in family life, education, employment, motherhood and situations of violence – both enable and erode self confidence and esteem. The challenges to women’s mental wellbeing cut across age and class differences and have profound impacts on the material conditions of women’s lives throughout the life course. This is in turn a driver of inequality that is often under-recognised in mainstream policy. Based on feminist and ethnographically informed research with over five hundred women Gendering women provides a critical link between gender theory and the lived realities of women’s daily lives and will appeal to students and academics in sociology and social sciences.